Confirmation of multiple seizure susceptibility QTLs on chromosome 15 in C57BL/6J and DBA/2J inbred mice - Ferraro, T. N. (American Physiological Society, 2010)
To confirm seizure susceptibility (SZS) quantitative trait loci (QTLs) on chromosome (chr) 15 identified previously using C57BL/6J (B6) and DBA/2J (D2) mice and to refine their genomic map position, we studied a set of three congenic strains in which overlapping segments of chr 15 from D2 were transferred onto the B6 background. We measured thresholds for generalized electroshock seizure (GEST) and maximal electroshock seizure (MEST) in congenic strains and B6-like littermates and also tested their responses to kainic acid (KA) and pentylenetetrazol (PTZ). Results document that MEST is significantly lower in strains 15M and 15D, which harbor medial and distal (telomeric) segments of chr 15 (respectively) from D2, compared with strain 15P, which harbors the proximal (acromeric) segment of chr 15 from D2, and with control littermates. Congenic strains 15P and 15M exhibited greater KA SZS compared with strain 15D and B6-like controls. All congenic strains were similar to controls with regard to PTZ SZS. Taken together, results suggest there are multiple SZS QTLs on chr 15 and that two QTLs harbor gene variants that affect MEST and KA SZS independently. The MEST QTL is refined to a 19 Mb region flanked by rs13482630 and D15Mit159. This interval contains 350 genes, 183 of which reside in areas where the polymorphism rate between B6 and D2 is high. The KA QTL interval spans a 65 Mb region flanked by markers D15Mit13 and rs31271969. It harbors 83 genes in highly polymorphic areas, 310 genes in all. Complete dissection of these loci will lead to identification of genetic variants that influence SZS in mice and provide a better understanding of seizure biology.